The August 2011 flood in Ibadan, Nigeria: anthropogenic causes and consequences (2012)
Determining when and where flood strikes can be a daunting task. Apart from heavy and prolonged rainfalls and river overflows, there are anthropogenic causal factors of flooding. These anthropogenic factors are significantly variable and exacerbate floods, but may be difficult to measure. This study aims to unravel some of the anthropogenic factors, particularly with respect to their contributions to the flood in Ibadan City on 26 August 2011. Data were collected through structured questionnaire and key informant interviews. The August 2011 Ibadan flood was perhaps the worst in the history of this ancient city. Twelve anthropogenic factors are broadly identified as having contributed to the flood and the flood had five major consequences. Some policy implications that can help prevent future flood occurrence are outlined.